2015
DOI: 10.3892/or.2015.4043
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 promotes human cholangiocarcinoma cell proliferation, migration and invasion through the upregulation of β-catenin expression via EP3-4 receptor

Abstract: Abstract. Prostaglandin E2 (PGE2) is involved in cholangiocarcinoma cell proliferation, migration and invasion through E prostanoid receptors, including EP1, EP2 and EP4. However, the functions and the mechanisms of those splice variants of EP3 receptors in promoting liver cancer cell growth and invasion remain to be elucidated. In our previous studies, four isoforms of EP3 receptors, EP3-4, EP3-5, EP3-6 and EP3-7 receptors, were detected in CCLP1 and HuCCT1 cells. However, the functions of these receptors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
3
13
0
1
Order By: Relevance
“…The constitutively active β-catenin signaling pathway results in disturbed cell-to-cell adhesion and consequent upregulation of the migration potential of tumor cells. Moreover, some studies demonstrated that PGE2 could have pro-oncogenic actions including proliferation and metastasis by stimulating β-catenin-mediated transcription in carcinogenesis (22,42). The data presented in the present study provide evidence that meloxicam exerts its anti-migration effects through downregulation of nuclear accumulation of β-catenin and inhibiting the phosphorylation of GSK-3β.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The constitutively active β-catenin signaling pathway results in disturbed cell-to-cell adhesion and consequent upregulation of the migration potential of tumor cells. Moreover, some studies demonstrated that PGE2 could have pro-oncogenic actions including proliferation and metastasis by stimulating β-catenin-mediated transcription in carcinogenesis (22,42). The data presented in the present study provide evidence that meloxicam exerts its anti-migration effects through downregulation of nuclear accumulation of β-catenin and inhibiting the phosphorylation of GSK-3β.…”
Section: Discussionsupporting
confidence: 68%
“…Disturbance of the complex promotes the phosphorylation of β-catenin by glycogen synthase kinase-3β (GSK-3β) and casein kinase 1α (CK1α) leading to the proteasomal degradation of β-catenin (19). β-catenin accumulation eventually leads to its nuclear translocation and then it binds to members of the TCF/LEF family of transcription factors, thus regulating expression of various target genes which are associated with many cellular processes including cell survival, proliferation, and migration (20)(21)(22). Meloxicam (Mel) is an NSAID that specifically inhibits COX-2.…”
Section: Meloxicam Suppresses Hepatocellular Carcinoma Cell Proliferamentioning
confidence: 99%
“…[44][45][46][47][48] β-catenin is an important player in the Wnt signaling pathway and its nuclear translocation results in regulating the expression of various target genes associated cellular processes such as cell survival, proliferation, and migration. 49,50 Our present study revealed that Dsh-003 could block PGE2-induced cell migration effect, finally, and reversed PGE2 induced β-catenin signaling pathway. Therefore, our data indicate that Dsh-003 inhibits PGE2-induced migration effects and β-catenin pathway in HA22T cells.…”
Section: Discussionsupporting
confidence: 54%
“…PGE2 is involved in the β‐catenin pathway and therefore accelerates the progression of cancers of breast, neuroblastoma, hepatocellular carcinoma, and colorectal cancer . β‐catenin is an important player in the Wnt signaling pathway and its nuclear translocation results in regulating the expression of various target genes associated cellular processes such as cell survival, proliferation, and migration . Our present study revealed that Dsh‐003 could block PGE2‐induced cell migration effect, finally, and reversed PGE2 induced β‐catenin signaling pathway.…”
Section: Discussionsupporting
confidence: 52%
“…The presence of EP4 and EGFR signaling cross-talk is supported by the fact that inhibition of EGFR reverses the positive effect of EP4 stimulation on matrix degradation, and the other way around. A number of papers proposed the EGFR pathway as effector for EP4-mediated signaling pathways in cancer (Du et al, 2015; Parida et al, 2016; Tveteraas et al, 2012; Yokoyama et al, 2013; M. Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%